How gender and religion impact uptake of family planning: results from a qualitative study in Northwestern Tanzania - Radhika Sundararajan; Lauren Mica Yoder; Albert Kihunrwa; Christine Aristide; Samuel E. Kalluvya; David J. Downs; Agrey H. Mwakisole; Jennifer A. Downs (BMC, 2019)
Abstract Background Women in Tanzania report a high unmet need for both information about and access to family planning. Prior studies have demonstrated the complex and variable relationship between religious faith and beliefs about family planning in sub-Saharan Africa. We hypothesized that a major reason for the poor uptake of family planning in Tanzania is that women and their partners are uncertain about whether pregnancy prevention is compatible with their religious beliefs. Methods Twenty-four focus group discussions with 206 participants were conducted in Mwanza, Tanzania between 2016 and 2017: six groups were conducted among Christian men, six among Christian women, six among Muslim men, and six among Muslim women. Among Christians, 98% were Protestants. Focus groups were also divided by gender and religion to facilitate discussion about gender-specific and religion-specific factors influencing family planning utilization. Qualitative data were analyzed using a thematic, phenomenological approach. Results We identify two important themes regarding the intersections of religion and family planning practices. First, we report that dynamics of family planning are experienced differently based on gender, and that male authority conflicts with female embodied knowledge, leading to negotiation or covert contraceptive use. Second, religious acceptability of family planning methods is of central importance, though participants differed in their interpretations of their religion's stance on this question. Most who found family planning incompatible with their faith affirmed their responsibility to give birth to as many children as God would give them. Others found family planning to be acceptable given their moral responsibility to care for and protect their children by limiting the family size. Conclusions Both religious tradition and gender dynamics strongly influence the uptake of family planning, with a wide range of interpretations of religious traditions affecting the perceived acceptability of family planning. Regardless of gender or religious affiliation, participants were unified by a desire to live according to religious tradition. Future efforts to improve uptake of family planning are likely to have maximal impact if they are tailored to inform, involve, and empower male heads of households, and to address questions of religious acceptability.